New perspectives on arson and firesetting: the human-fire use relationship - Horsley, Faye K. (New frontiers in forensic psychology, 2022)
"New Perspectives on Arson and Firesetting: The Human-Fire Use Relationship is the first forensic text to move away from a sole focus on anti-social fire setting. The author presents a broader investigation of the role of fire in human life with a view to informing research and practice. This book examines the evolutionary, psychological and social significance of fire. Drawing on interdisciplinary literature and original research data, it challenges the existing understanding of arson and fire setting. A new concept - fire use - is introduced, which is conceptualised as sitting on a continuum from non-criminalised to criminalised behavior. The author combines her experience as a practitioner forensic psychologist with her own research to consider the practical application of an alternative perspective. This includes a particular focus on the assessment and treatment of fire setters and a call for a socially informed approach to prevention. The forensic scope, applied focus, and emphasis on the importance of interdisciplinary research and practice makes New Perspectives on Arson and Firesetting essential reading for students in fields such as anthropology, sociology, criminology, and psychology, as well as interdisciplinary scholars, forensic practitioners, and allied professionals"--